A Survey on Digital Content Sentiment Features and Techniques - Sangule, Sukhlal; Phulre, Sunil (International Journal of Computer Sciences and Engineering, 2020)
Sentiment analysis is one of the fastest growing research areas in computer science, making it challenging to keep track of all the activities in the area. In recent years, sentiment analysis has shifted from analyzing online product reviews to social media texts from Twitter and Facebook. Many topics beyond product reviews like stock markets, elections, disasters, medicine, software engineering, etc. extend the utilization of sentiment analysis. This paper discusses in details the various techniques to Sentiment Analysis, so class of sentiment identify accurately. Text mining pre- processing steps were also discussed for generation of features. This paper provides previous researcher work in detail. Challenges of sentiment mining were also summarized.